2016
DOI: 10.1353/jda.2016.0010
|View full text |Cite
|
Sign up to set email alerts
|

Dependence between stock market and foreign exchange market in South Asia: A Copula-Garch approach

Abstract: The paper studies the dependence pattern between stock market and foreign exchange market of three South Asian countries; namely Bangladesh, India and Sri Lanka by using five copula functions, to reveal asymmetric dependence structure. This paper focuses South Asia because of its promise as portfolio investment destination. The dependence structure between stock market and foreign exchange market assists MNCs, private equity firms, international portfolio managers and policy makers in international investment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Contrastingly, innovations of the model are negative and negatively decreasing suggesting the decreasing impact from the innovations or system shocks on the future stock returns. The behaviour of returns and innovations estimated are complementary to the findings of Kamal and Haque (2016) on Sri Lankan stock market behaviour post crisis. Moreover, the rapid decline of the prior returns and innovation on future stock returns provide confirmation to the findings of Arsalan, et.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Contrastingly, innovations of the model are negative and negatively decreasing suggesting the decreasing impact from the innovations or system shocks on the future stock returns. The behaviour of returns and innovations estimated are complementary to the findings of Kamal and Haque (2016) on Sri Lankan stock market behaviour post crisis. Moreover, the rapid decline of the prior returns and innovation on future stock returns provide confirmation to the findings of Arsalan, et.…”
Section: Resultsmentioning
confidence: 62%
“…Further, Sans-Cipollitti (2020) identified that ARMA-GARCH approach comparatively provided higher accuracy in stock index prediction. Kamal and Haque (2016) modeled the volatility of the Indian, Bangladesh and Sri Lankan stock markets in ARMA-GARCH to determine the fact that in the South Asian markets' volatility subsided promptly post crisis. Locally, Zhang and Nadarajah (2018) analysed CSE returns from 1985 to 2017 to conclude that the ARMA-APARCH modelling is efficient in forecasting volatility of the Sri Lankan market based on its log likelihood.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study employs the copula-TARCH method for considering such asymmetric dependence. As shown in past studies (e.g., Kamal and Haque, 2016; Kresta 2013), this class of methods has good statistical performance when the process follows a distribution with fat tails and displays volatility clustering, which is the case for currency returns. As the purpose of this article is to examine currency risks due to unexpected and excessive RMB movements, tail dependence remains the focus of analysis.…”
Section: Introductionmentioning
confidence: 60%
“…In recent years, a number of researchers have started to extend the GARCH method to the copula-GARCH framework, which has a better ability to capture the dependence structure between two financial assets, by taking into account their volatility. Kamal and Haque (2016) applied the copula-GARCH approach to study the asymmetric dependence structure between daily returns of benchmark stock index and exchange rate in India, Bangladesh and Sri Lanka. Their results showed that both stock and foreign exchange markets suffer higher volatility when market news are positive.…”
Section: Introductionmentioning
confidence: 99%
“…Exchange rate uncertainty: Exchange rates affects stock returns negatively through capital mobility 5 ( Frankel, 1983 ; Liang et al, 2013 ; Kamal and Haque, 2016 ). Exchange rate volatility affects stock return volatility ( Kasman et al, 2011 ).…”
Section: Econometric Methods and Datamentioning
confidence: 99%